Genetic heterogeneity in Rieger eye malformation. Issue 4 (April 1994) - Legius, E; de Die-Smulders, C E; Verbraak, F; Habex, H; Decorte, R; Marynen, P; Fryns, J P; Cassiman, J J
Abstract : A three generation family with Rieger eye malformation sequence is described. No other abnormalities were present apart from the eye malformation. Linkage to EGF and D4S193 localised in 4q25 was excluded and this indicates that Rieger eye malformation is genetically different from typical Rieger syndrome with teeth and umbilical anomalies.